Flexible, Stretchable, and Multifunctional Electrospun Polyurethane Mats with 0D‐1D‐2D Ternary Nanocomposite‐Based Conductive Networks. (6th December 2020) - Huang, Jieyu; Zhao, Min; Hao, Yi; Li, Dawei; Feng, Jingdong; Huang, Fenglin; Wei, Qufu
Abstract: A multifunctional electrospun polyurethane mat with unique multi‐dimensional conductive networks is fabricated with carbon nanotubes (CNT) and MXene weight ratio of 1:2 and twice Ag adsorption–reduction processes. 0D silver nanoparticles are designed to be loaded on 2D MXene sheets and combined with 1D CNT in ternary conductive networks. The obtained composite mats present outstanding strain sensitivity, wide strain sensing range, shorter response time, and long‐term stability and repeatability, precisely detecting large‐scale and subtle human motions. Triggered by the unique conductive networks, the mats also exhibit excellent Joule heating and electromagnetic interference shielding performance. The development of flexible, stretchable, and multifunctional mats is highly promising for smart wearable devices of integrated strain sensing, thermal management, and electromagnetic shielding. Abstract : A flexible, stretchable, and multifunctional electrospun polyurethane (PU) mat based on 0D‐1D‐2D multi‐dimensional conductive networks is fabricated. The PU–carbon nanotubes–MXene–silver nanoparticle (PU–CNT–M–Ag) mat presents integrated strain sensing, Joule heating, and electromagnetic interference shielding performances. Furthermore, the PU–CNT–M–Ag strain sensor can be used for detecting both subtle movements and large‐scale motions.